"Structural imprinting" of the cutaneous immune effector function. Issue 1 (2nd January 2021) - Ishitsuka, Yosuke; Roop, Dennis R.; Ogawa, Tatsuya
ABSTRACT: Keratinization provides tolerance to desiccation and mechanical durability. Loricrin, which is an epidermal thiol-rich protein, efficiently stabilizes terminally differentiated keratinocytes and maintains redox homeostasis. The discovery of the largely asymptomatic loricrin knockout (LKO) phenotype decades ago was rather unpredicted. Nevertheless, when including redox-driven, NF-E2-related factor 2-mediated backup responses, LKO mice provide opportunities for the observation of altered or "quasi-normal" homeostasis. Specifically, given that the tissue structure, as well as the local metabolism, transmits immunological signals, we sought to dissect the consequence of truncated epidermal differentiation program from immunological perspectives. Through a review of the aggregated evidence, we have attempted to generate an integrated view of the regulation of the peripheral immune system, which possibly occurs within the squamous epithelial tissue with truncated differentiation. This synthesis might not only provide insights into keratinization but also lead to the identification of factors intrinsic to the epidermis that imprint the immune effector function.